Immune responses to hepatitis B vaccination after hematopoietic stem cell transplantation in pediatric and young adult patients. Issue 10 (4th September 2020) - Chaichotjinda, Krittiya; Anurathapan, Usanarat; Boonsathorn, Sophida; Chaisavaneeyakorn, Sujittra; Treepongkaruna, Suporn; Techasaensiri, Chonnamet; Apiwattanakul, Nopporn
Abstract: Background: Hematopoietic stem cell transplantation (HSCT) recipients require hepatitis B (HBV) revaccination. Hepatitis B surface antibody (anti‐HBs) seroconversion rates after revaccination range from 64% to 79% in these patients. The seroconversion rate and factors associated with non‐seroconversion have not been clearly elucidated in pediatric and young adult recipients after HSCT. Objectives: To evaluate anti‐HBs seroconversion rates in pediatric and young adult patients revaccinated after HSCT, and to identify factors associated with non‐seroconversion. Method: The current study was prospective and cross‐sectional. Post‐HSCT recipients aged ≤25 years who had completed a course of three HBV revaccinations were recruited, and their anti‐HBs titers were assessed. Non‐seroconverted patients were administered a fourth vaccination. Those who subsequently remained seronegative were administered two additional vaccinations. Those who remained seronegative after all six vaccinations were defined as non‐responders. Results: A total of 118 patients were enrolled. The HBV‐containing vaccines used included DTaP‐IPV‐HBV‐Hib, DTwP‐HBV‐Hib, and monovalent vaccines. The anti‐HBs seroconversion rate after three revaccinations was 82% (95% confidence interval [CI], 73.7‐89.2). One patient (0.8%) was classified as non‐responder. Factors associated with non‐seroconversion after three revaccinations included cytomegalovirus (CMV) reactivation (odds ratio [OR] 10.63, 95% CI 1.16‐97.00), anti‐HBs seronegativity before HSCT (OR 7.01, 95% CI 1.55‐31.78) and three DTwP‐HBV‐Hib revaccinations (OR 11.71, 95% CI 1.43‐96.26). Conclusion: In the current study the anti‐HBs seroconversion rate after three HBV revaccinations was excellent. CMV reactivation, anti‐HBs seronegativity before HSCT, and three DTwP‐HBV‐Hib revaccinations were associated with non‐seroconversion, but the non‐responder rate was low.